CRACK PROPAGATION BEHAVIOR OF OIL WELL TUBING STEEL UNDER CORROSION FATIGUE LOADING IN CO2-CL-CORROSIVE ENVIRONMENT - LI Zhen; WANG WenTao; WANG JianCai; CUI Lu; DOU YiHua (Jixie qiangdu, 2016)
Corrosion medium such as CO2-Cl-causing corrosion pits in the pipe wall exist usually in the service environment of well tubing. These pits will become the fatigue source of the fatigue damage of oil tubing under cyclic loading. In this paper,tubing steel of 13 Cr used in oil well is selected as research object,and CO2-Cl- corrosive environment is selected for simulating the service condition of tubing. In the corrosive environment,fatigue experiments are performed on standard CT specimens to study crack propagation behavior of 13 Cr steel. Crack propagation rate of the 13 Cr steel under cyclic loading is measured in air environment,in Cl- environment and in CO2-Cl- corrosive environment respectively. The change of corrosion fatigue crack propagation rate under the three environment condition is carried out. With the observation of fracture morphology, the mechanism of corrosion fatigue failure of the 13 Cr steel in the CO2-Cl- corrosive environment is analyzed.